2016
DOI: 10.1037/pmu0000141
|View full text |Cite
|
Sign up to set email alerts
|

Expressivity, affective nuance, and presentation modality in a performer-to-audience communication.

Abstract: It is a given that a live concert is fundamentally different from a recorded live performance, but we wanted to investigate in a controlled setting how different renditions of the same piece of music affected an audience. In our previous case study using Rachmaninoff's pieces, a pianist expressed richer affective nuances when he performed his artistic rendition of the piece than his contrived deadpan (i.e., mechanical) and exaggerated renditions (Shoda & Adachi, 2012). The primary goal of the present study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This study adds to the fledgling literature examining music listening in concert settings (Egermann et al, 2011; Shoda and Adachi, 2012, 2015, 2016; Fancourt and Williamon, 2016; Shoda et al, 2016). It provides unique insight into how live music is experienced in ecologically valid conditions, and how that experience is expressed through body movement.…”
Section: Discussionmentioning
confidence: 82%
“…This study adds to the fledgling literature examining music listening in concert settings (Egermann et al, 2011; Shoda and Adachi, 2012, 2015, 2016; Fancourt and Williamon, 2016; Shoda et al, 2016). It provides unique insight into how live music is experienced in ecologically valid conditions, and how that experience is expressed through body movement.…”
Section: Discussionmentioning
confidence: 82%
“…These results indicate that visual input contributes significantly to the perception and appreciation of a musical performance, from which it can be inferred that DMI performances that present conflicting or confusing audiovisual information might be less effective at communicating musical intentions to an audience. Vuoskoski, Gatti, Spence and Clarke (2016) and Shoda and Adachi (2016) have provided contrasting results on this matter, reporting stronger emotional responses to audio-only conditions. However, these two studies both used music from the Romantic era (Brahms and Rachmaninoff respectively) that employ a musical idiom familiar to most listeners.…”
Section: Empirical Research On Audiovisual Music Perceptionmentioning
confidence: 99%
“…We also planned to assess whether such intervention in the form of telemedicine would be viable. Considering research indicated that the interactivity of live music was more strongly associated with positive outcomes (24)(25)(26), we chose live, over recorded music. Due to mandatory COVID-19 precautions in the hospital, musical activities were organized virtually.…”
Section: Introductionmentioning
confidence: 99%